The Challenges of Managing Medical Records in Pantai Hospital Kuala Lumpur - Md Zali, Mastura; Ramli, Nurain; Zainal Abidin, Nurul Amirah; Fathilah, Raihana (Bachelor of Information Science (HONS.) Records Management, 2014)
Pantai Hospital Kuala Lumpur (PHKL) is implementing the traditional record management system. In managing the record there is number of challenges in run the management. These paper are conducted is to investigate the challenges in managing record at PHKL at the same time it's to find out the strategy to overcome the challenges. The target population is a person who is related with the management of the record the Medical Records Department in the PHKL. Moreover, the population size in this research is all staff in the medical record department. Thus, all the staffin the department is selected to be as respondent. The types of research design are quantitative and methods of data collection use in analysis are the questionnaire. The type of questionnaire use is the closes ended question. In the close question it use the straight forward respond, dichotomous, and likers scale (scale for measuring the attitude). The research data are collectedfrom all staffin the Medical Record Department at PHKL. Thus, the number of respondent is twenty 21. However only 20 copies of questionnaires are return back to the researcher. In these research the key finding into know what the challenges and how it being overcome. Therefore, after collecting and analyze the data the result are answering the research question.